Genome-wide analysis of RWP-RK transcription factor family reveals its roles in nitrogen response in rice (Oryza sativa) - Du, Mei; Guo, Ziwen; Gong, Siyu; Xu, Liangwei (Frontiers in Plant Science, 2025)
IntroductionThe RWP-RK transcription factor family plays a pivotal role in nitrogen response and gametophyte development. Despite its biological importance, the evolutionary relationships and functional characteristics of RWP-RK genes in rice remain incompletely understood. This study aimed to investigate the structure, classification, expression patterns, and potential regulatory roles of RWP-RK transcription factors in rice (Oryza sativa), with a focus on their involvement in nitrogen signaling and reproductive development.MethodsA comprehensive genome-wide analysis was conducted to identify RWP-RK genes in rice. A total of 13 genes encoding 14 proteins, including two alternative splicing variants of OsNLP5, were identified and mapped across 8 of the 12 rice chromosomes. Phylogenetic analysis was used to classify the proteins into subfamilies, and gene/protein structure characteristics were examined, including coding sequence length, exon number, and domain composition. Collinearity analysis was performed to explore evolutionary relationships between rice and Arabidopsis. Promoter regions of the RWP-RK genes were analyzed for cis-regulatory elements, and tissue-specific as well as nitrogen-responsive gene expression patterns were evaluated using expression profiling.ResultsPhylogenetic analysis grouped the 14 RWP-RK proteins into four clades: groups 1–3 were assigned to the NLP subfamily and group 4 to the RKD subfamily. NLP members contained both RWP-RK and PB1 domains, while RKD proteins possessed only the RWP-RK domain. Structural analysis revealed that NLP genes generally have longer CDS, more exons, and larger proteins than RKD genes. Collinearity analysis suggested that rice and Arabidopsis RWP-RK genes share a common ancestor, with evidence of gene recombination and species-specific divergence. Promoter analysis revealed numerous hormone- and stress-responsive cis-elements. Expression profiling showed that OsNLP genes are broadly expressed in all tissues, whereas OsRKD genes are predominantly active in reproductive organs. Upon nitrogen resupply after nitrogen starvation, expression levels of all OsNLP genes and three OsRKDs (OsRKD1, OsRKD3, OsRKD5) showed dynamic changes.DiscussionThe findings provide new insights into the classification, structure, and expression dynamics of the RWP-RK transcription factor family in rice. The distinct domain architectures and expression patterns between the NLP and RKD subfamilies suggest functional divergence, with NLP genes potentially playing broader roles in general nitrogen regulation, while RKD genes may be more specialized for reproductive development. The nitrogen-responsive expression changes highlight the potential regulatory role of these transcription factors in nutrient signaling. Overall, this study lays a valuable foundation for future functional investigations into the OsRWP-RK family's roles in nitrogen response and gametophyte development in rice.